The Sugarcane (Saccharum officinarum L.) Bud Chip Growth on the Giving of Different NAA Concentrations and Nitrogen Fertilizer Doses - Setiawan, Bagus; Fuskhah, Eny; Karno (Journal of Tropical Crop Science and Technology, 2020)
This research aimed to assess the effect of Naphthalene Acetic Acid (NAA) and nitrogen fertilizer on the growth of sugarcane (Saccharum officinarum L.) bud chips. The research was conducted using a 4 x 4 factorial design with the basis of a completely randomized design (CRD) of 3 replications. The first factor was the concentration of NAA which consisted of 0 ppm (without NAA), 50 ppm, 100 ppm, and 150 ppm. The second factor was the dose of nitrogen fertilizer which consisted of a dose of 45 kgN/ha, 90 kg N/ha, 135 kg N/ha, and 180 kg N/ha. The growth parameters observed included plant height, number of leaves, tillers, root dry weight, and shoot dry weight. The data were analyzed by analysis of variance and continued with Duncan’s test (Duncan’s Multiple Range Test) at a 5% level. The results showed that the application of NAA could not increase the growth of sugarcane bud chips on all parameters. Application of nitrogen fertilizer at a dose of 45 kg N/ha could increase plant height growth, number of leaves, root dry weight, and shoot dry weight. Nitrogen fertilizer with a dose of 180 kg N/ha reduced the growth of sugarcane bud chips. The higher dose of nitrogen fertilizer inhibited the growth of sugarcane bud chips.